Adsorptive separation and recovery of triacetic acid lactone from fermentation broth. (15th September 2022) - Singh, Ramkrishna; Bhagwat, Sarang S.; Viswanathan, Mothi Bharath; Cortés‐Peña, Yoel R.; Eilts, Kristen K.; McDonough, Grace; Cao, Mingfeng; Guest, Jeremy S.; Zhao, Huimin; Singh, Vijay
Abstract: Triacetic acid lactone (TAL), an emerging bioprivileged molecule, can be produced microbially and further chemically upgraded to several high‐value chemicals. In this work, several acidic and basic ion‐exchange resins and activated charcoal were evaluated for their ability to adsorb microbially produced TAL. Activated charcoal and a weak base resin, Dowex 66, showed similar TAL adsorption capacity of 0.18 ± 0.002 g/g. At 15% w/v activated charcoal, about 98% of TAL present in fermentation broth could be adsorbed. Further, ethanol washing allowed recovery of 72% of adsorbed TAL. A biorefinery producing TAL from sucrose was designed, simulated, and evaluated (through technoeconomic analysis) under uncertainty, for an estimated TAL minimum product selling price (MPSP) of $4.27/kg ($3.71–4.94/kg; 5th–95th percentiles) given the current state of technology and $2.83/kg ($2.46–3.29/kg) following potential near‐term improvements to fermentation. This work provides an adsorptive process for the recovery of microbially produced TAL that can be upgraded chemically to a range of industrial products. © 2022 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.